PENYULUHAN HUKUM TENTANG SOSIALISASI KESADARAN MASYARAKAT DALAM NEGARA HUKUM BERDASARKAN UUD TAHUN 1945 - Muzayanah Muzayanah; Rochmani Rochmani; Safik Faozi; Sukarman Sukarman (Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
Community Service Activities are the implementation of the Tri Dharma of Higher Education that must be carried out in order to provide understanding to the community, especially to Prolanis Patients at the